Striatal dynamics represent subjective time - Gouvêa, Thiago Santos (2018)
Time is a fundamental dimension of the environment. The ability to estimate the passage of time is essential for both learning and performance of adaptive behavior in natural situations. Yet, how this ability is implemented in the brain is poorly understood